Gender Differences in COVID-19 Anxiety Syndrome Among Filipino Nursing Students (JKG (JURNAL KEPERAWATAN GLOBAL), 2021)
Background: The global COVID-19 outbreak has affected all sectors of society. Nursing students were not exempted. This study examined COVID-19 anxiety syndrome among Filipino nursing students and whether significant differences existed according to gender. Methods: This cross-sectional study used the COVID-19 Anxiety Syndrome Scale (C-19ASS) as the primary tool for data collection. Significant gender differences were tested using the Mann-Whitney U test. Results: Results showed that the composite score in the C-19ASS was 3.92 (SD=.69) indicating a moderate to a high level of anxiety syndrome features associated with COVID-19 among nursing students. The mean scores in the preservation and avoidance factors were 3.94 (SD=.76) and 3.88 (SD=.91), respectively. Female nursing students had a significantly higher (p=.004) COVID-19 anxiety syndrome compared to male nursing students. Conclusion: The global outbreak of COVID-19 brought about extraordinary anxiety syndrome and stressful situations among nursing students. Nursing students, particularly female students, may benefit from additional support and guidance during the COVID-19 pandemic.
Keywords: anxiety; COVID-19; gender differences; nursing; students